2006
DOI: 10.1111/j.1532-5415.2006.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Medications for Chronic Diseases in the Oldest of Community‐Dwelling Older Frail Japanese

Abstract: Among community-dwelling frail older people, the rate of polypharmacy is lower in the oldest members than in the younger ones. The underuse of prescribed medications for chronic diseases/conditions of frail older people is common but not for all conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 25 publications
2
48
3
Order By: Relevance
“…It is generally recognized that health care inequalities exist, which may be classifiable using socioeconomic measures, or by ethnic group or gender [6], but it is important to consider whether such inequalities exist for different age groups too. Some studies, for example, have identified an “under-prescription” phenomenon for the chronically ill among the oldest old [7], and this also relates to cases of coronary heart disease (CHD) [8]. The differences identified could represent an excellent starting point for efforts to better define optimum care or best practices, to design care processes that meet patients’ needs [3], and to improve the quality of primary health care in terms of an equitable management of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that health care inequalities exist, which may be classifiable using socioeconomic measures, or by ethnic group or gender [6], but it is important to consider whether such inequalities exist for different age groups too. Some studies, for example, have identified an “under-prescription” phenomenon for the chronically ill among the oldest old [7], and this also relates to cases of coronary heart disease (CHD) [8]. The differences identified could represent an excellent starting point for efforts to better define optimum care or best practices, to design care processes that meet patients’ needs [3], and to improve the quality of primary health care in terms of an equitable management of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Medication underutilization is defined as the omission of an indicated and potentially beneficial medication for the treatment or prevention of a disease or condition 1,2,4,7,8. Most previous studies in older adults have focused on omission of medications for specific conditions using explicit criteria 5,6,9,10. Some examples of underuse from these studies included not prescribing platelet inhibitors for patients with a history of stroke or calcium supplements for those at risk of osteoporotic fracture 3,6,8.…”
Section: Introductionmentioning
confidence: 99%
“…In the oldest group of elderly patients the prescription of preventive therapy is often omitted (30,31). Surprisingly, results of multivariate analysis showed that the oldest patients of our study group (≥ 85 years) had higher probability of receiving gastroprotective medication in comparison with younger elderly (< 85 years).…”
Section: Discussionmentioning
confidence: 65%